2012
DOI: 10.1016/j.ijrobp.2011.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Control Outcomes After Hypofractionated and Single-Dose Stereotactic Image-Guided Intensity-Modulated Radiotherapy for Extracranial Metastases From Renal Cell Carcinoma

Abstract: Purpose To report tumor local progression-free outcomes following treatment with single-dose image-guided intensity-modulated radiotherapy (SD-IGRT) and hypofractionated regimens for extracranial metastases from renal cell primary tumors. Methods and Materials Between 2004 and 2010, a total of 105 lesions from renal cell carcinomas were treated with either SD-IGRT to prescription doses of 18–24 Gy (median, 24 Gy) or hypofractionation (3 or 5 fractions) with prescription doses ranging between 20 and 30 Gy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(113 citation statements)
references
References 27 publications
6
105
1
1
Order By: Relevance
“…We have described the best available contemporary evidence base, from which 12 Amiraliev et al (2012) 23 Brinkmann et al (2007) 29 Eggener et al (2008) 27 Fokas et al (2010) 36 Fuchs et al (2005) 35 Hunter et al (2012) 34 Ikushima et al (2000) 37 Kwak et al (2007) 30 Lee et al (2006) 32 Pretalia et al (2010) 24 Russo et al (2007) 31 Staehler et al (2009) 26 Staehler et al (2010) 25 Zelefsky et al (2012) 33 Zerbi et al (2008) Review some conclusions can be made, and identifi ed knowledge gaps that can only be addressed through well-designed, prospective comparative studies. However, there are several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have described the best available contemporary evidence base, from which 12 Amiraliev et al (2012) 23 Brinkmann et al (2007) 29 Eggener et al (2008) 27 Fokas et al (2010) 36 Fuchs et al (2005) 35 Hunter et al (2012) 34 Ikushima et al (2000) 37 Kwak et al (2007) 30 Lee et al (2006) 32 Pretalia et al (2010) 24 Russo et al (2007) 31 Staehler et al (2009) 26 Staehler et al (2010) 25 Zelefsky et al (2012) 33 Zerbi et al (2008) Review some conclusions can be made, and identifi ed knowledge gaps that can only be addressed through well-designed, prospective comparative studies. However, there are several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies assessed local treatments of metastases from renal cell carcinoma in various organs, 12,24,26,27,[29][30][31][32] of which the most common sites were lung, bone, liver, and brain, and less common sites were pancreas, adrenal gland, lymph nodes, thyroid gland, spleen, ethmoid sinus, and skin (table 1). Other studies also assessed local treatments for metastases from renal cell carcinoma in bone (including the vertebrae), 33 29 used treatment beforehand. In one study, 30 systemic treatment was not used.…”
Section: Review Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective analysis of 105 cases of metastatic renal cell carcinomas treated (59 spinal lesions) with either hypofractionated or high dose IGRT (dose range 18-24 Gy), Zelefsky et al confirmed a strong predictive value of high prescription dose. 33 The overall 3-year actuarial local progression-free survival for all lesions was 44%. The 3-year local control for high single-dose (24 Gy), low single-dose (<24 Gy), and hypofractionation were 88%, 21%, and 17%, respectively (high single dose versus low single dose, p = 0.001).…”
Section: Outcomes Of Single Dose Sbrt For Spine Tumorsmentioning
confidence: 92%